Some Characterizations Of Surfaces Generated by Two Curves In Heis 3 - Suroğlu, Gülden Altay (My University, 2018)
In this paper, some characterizations of surfaces which are constructed by using the group operation in3 Heis are given. Then, a new classification for minimal factorable surfaces in 3 Heis is obtained.
Keywords: Matematik